Nursing care for patients with bone metastases undergoing radiotherapy: a scoping review - Taís dos Passos Sagica; Sandra Suely Silva de Oliveira; Odenilce Vieira Pereira; Aline Maria Pereira Cruz Ramos (Universidade Federal do Ceará, 2023)
Objective: to map studies on nursing care for patients with bone metastases undergoing radiotherapy. Methods: scoping review conducted in nine databases, according to the guidelines of the Joanna Briggs Institute. Scientific articles available for full open access, in any language, regardless of the method used, were included. Results: 13 studies were analyzed, with a predominance of literature reviews. The themes were: health education to patients and companions about events related to the skeleton; pain assessment and management; prevention of pathological fractures; management of spinal cord compression; assessment of hypercalcemia; ensuring safety in the administration of oral bisphosphonates; quality of life assessment; and monitoring of progress, adverse events, and therapeutic outcomes. Conclusion: nurses provide important ongoing support to patients, monitor progress, side effects, and therapeutic outcomes, and prevent and manage skeletal-related events. Contributions to practice: the study highlighted the main nursing care to patients with bone metastases in radiotherapy treatment, being relevant to give theoretical subsidy to professionals directing their assistance, especially in the oncology area.